Assessment of genetically modified maize 1507 × MIR162 × MON810 × NK603 and subcombinations, for food and feed uses, under Regulation (EC) No 1829/2003 (application EFSA‐GMO‐NL‐2015‐127). (13th January 2021) - ,; Naegeli, Hanspeter; Bresson, Jean‐Louis; Dalmay, Tamas; Dewhurst, Ian Crawford; Epstein, Michelle M; Firbank, Leslie George; Guerche, Philippe; Hejatko, Jan; Moreno, Francisco Javier; Mullins, Ewen; Nogué, Fabien; et al.
Abstract: Maize 1507 × MIR162 × MON810 × NK603 (four‐event stack maize) was produced by conventional crossing to combine four single events: 1507, MIR162, MON810 and NK603. The GMO Panel previously assessed the four single events and six of the subcombinations and did not identify safety concerns. No new data on the single events or the six subcombinations that could lead to modification of the original conclusions on their safety were identified. The molecular characterisation, comparative analysis (agronomic, phenotypic and compositional characteristics) and the outcome of the toxicological, allergenicity and nutritional assessment indicate that the combination of the single maize events and of the newly expressed proteins in the four‐event stack maize does not give rise to food and feed safety and nutritional concerns. The GMO Panel concludes that the four‐event stack maize, as described in this application, is as safe as its non‐GM comparator and the non‐GM reference varieties tested. In the case of accidental release of viable seeds of the four‐event stack maize into the environment, this would not raise environmental safety concerns. The GMO Panel assessed the likelihood of interactions among the single events in the four maize subcombinations not previously assessed and concludes that these are expected to be as safe as the single events, the previously assessed subcombinations and the four‐event stack maize. The post‐market environmental monitoring plan and reporting intervals are in line with the intended uses of the four‐event stack maize. Post‐market monitoring of food/feed is not considered necessary. The GMO Panel concludes that the four‐event stack maize and its subcombinations are as safe as the non‐GM comparator and the tested non‐GM reference varieties with respect to potential effects on human and animal health and the environment.